(untitled) (International Journal of Medicine and Medical Sciences, 2019)
ARECA CATECHU L. (Arecaceae) nuts have been used in traditional medicine for the treatment of different diseases. The present study was performed to investigate the enhancement of ulcerogenic activity of ethanol extract from nuts of A. CATECHU in ethanol induced gastric mucosal injury in rats. Four groups of adult Sprague Dawley rats were orally pre-treated respectively with carboxymethyl cellulose (CMC) solution (ulcer control group), omeprazole 20 mg/kg (reference group), 250 and 500 mg/kg A. CATECHU nut extract in CMC solution (experimental groups) one hour before oral administration of absolute ethanol to generate gastric mucosal injury. After an additional hour, the rats were sacrificed and the ulcer areas of the gastric walls were determined. Grossly, the experimental groups exhibited significantly severe gastric mucosal injury compared to ulcer control group. Histological studies of the gastric wall revealed that experimental groups exhibited comparatively severe damage of gastric mucosa; along with edema and leucocytes infiltration of submucosal layer compared to ulcer control group. In conclusions, the present finding suggests that A. CATECHU nut extract enhanced ulcer production as ascertained grossly by significant increasing ulcer area, and histologically by comparatively increases in ulcer areas compared to ulcer control group.